Az együttműködés iránti attitűd hatása a közös tanulás és a közösséghez tartozás észlelésére kutatásalapú tanulásban részt vett tanulók körében - Molnár, Pál; Pintér, Henriett (Magyar Pedagógia, 2018)
In contemporary networked societies, collaboration is crucial to work and learning. Instructors are increasingly adopting collaborative strategies in the classroom. One prominent and wellresearched student-centred approach is inquiry-based learning. Still, few studies have investigated students’ attitudes towards collaboration and its effects on learning. Our study focuses on this issue. We investigated the relationships between attitude towards collaboration, perceived collaborative learning, learning in an online (blended) environment, and sense of community. Students formed groups and took part in a semester-long collaborative inquirybased learning scenario. We collected students’ data with a questionnaire before they started the collaborative inquiry and after they completed it. Then, we used structural equation modelling to test the hypothesized effects and correlations between the factors measured. Our results showed that before the collaborative inquiry-based learning scenario, many students stated that group work was effective and interesting, but not easy. After the inquiry, most of them regarded collaborative inquiry as positive and fruitful. Most of the students saw learning in an online environment as positive, while others did not. Further, the majority of the students valued the feedback they received from peers and felt that the discussions helped them to share their experiences and knowledge and to understand their peers’ viewpoints. Students more or less experienced a sense of community. Some of them stated that their interactions increased because they used an online learning environment, though, at the same time, others said they did not. In addition, some students felt they formed an important part of their learning community. As for the effects of attitude towards collaboration on collaborative learning and sense of community, results showed that students’ attitudes proved to have a strong effect on their perception of these factors. Overall, students whose attitude was positive towards collaboration perceived collaborative learning as effective and meaningful and felt they were part of a community. Our results suggest that instructors should consider their students’ attitudes towards collaboration when planning and managing collaborative learning settings. Instructors should not force group work on their learners, and/or they should use various methods to improve students’ attitudes. For example, it may be helpful to discuss the purpose of the collaboration, proper strategies, the role of peers, and feedback to students.